Caregiver Burden Assessment in Primary Congenital Glaucoma. Issue 3 (May 2013) - Dada, Tanuj; Aggarwal, Ashutosh; Bali, Shveta Jindal; Wadhwani, Meenakshi; Tinwala, Sana; Sagar, Rajesh
Purpose: To assess the magnitude of caregiver burden and depression in primary caregivers of patients with primary congenital glaucoma. Methods: Fifty-five primary caregivers of children diagnosed with primary congenital glaucoma were evaluated. The magnitude of burden on caregivers was assessed using a Caregiver Burden Questionnaire (CBQ). The overall aggregate burden and burden across 3 domains—socioeconomic, emotional, and psychological—was evaluated. Depressive symptomatology was evaluated using a Patient Health Questionnaire–9 (PHQ-9) standard questionnaire and graded from mild to severe. Results: The mean age of the presenting children was 8.11±46.71 months; all of them were male. The mean age of the study participants was 33.6±8.36 years (53 female, 2 male). Thirty-nine (71%) individuals were identified to have moderate aggregate burden and 3 (5%) had severe aggregate burden. Twelve (22%) subjects were noted to have moderate depression, while 6 of them (11%) had either severe or very severe grades of depression. Conclusions: Caregivers of patients with primary congenital glaucoma have significant emotional and psychological burden. Moderate to severe depression may be present in one-third of individuals giving primary care to children with congenital glaucoma.